Aktivitas Antibakteri Bakteri Asam Laktat yang diisolasi dari Makanan Tradisional Dangke, Kabupaten Enrekang, Sulawesi Selatan - Tanjung, Asbar; Tanfil, Ardi; Nur, Jumriah (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2024)
Introduction: Lactic acid bacteria (LAB) produce lactic acid as the end product of carbohydrate metabolism. LAB is known to have benefits, including balancing the microflora in the gut, is bacteriostatic, and is also reported to be able to stimulate the immune system. LAB can be isolated and characterized from various food products spread throughout Indonesia. Dangke is a food product in the form of processed cow's milk which is traditionally produced by the people of Enrekang Regency, South Sulawesi. Aims: To isolate and explore the characteristics of LAB both phenotype and genotype isolated from dangke as well as in vitro studies on the potential and mechanisms of their inhibition of the growth of pathogenic bacteria. Method: Research started with the process of collecting samples of dangke in Enrekang Regency, isolation and identification of indigenous LAB in dangke samples, characterization and continued with in vitro studies on the potential of LAB from dangke to inhibit bacterial growth. Results: LAB isolated from dangke macroscopic characteristics in the form of round colonies, mucoid texture, entire edge, elevation convex and translucent with a size of 2.2 mm. Microscopic characteristics in the form of rod-shaped gram-positive bacteria. Isolated LAB has the ability to grow in extreme conditions approaching intestinal conditions, namely growing in an environment with an acidic pH range of 3-5 and tolerant to bile salts. Secondary metabolites produced can inhibit the growth of S. aureus bacteria in vitro. Conclusion: LAB isolated from dangke have demonstrated significant potential for probiotic and antibacterial applications.